РЕГУЛЮВАННЯ ХАРАКТЕРИСТИК ЗАРЯДНОГО КОЛА ЄМНІСНОГО НАКОПИЧУВАЧА ЕНЕРГІЇ ЗМІНЕННЯМ ЙОГО ПОЧАТКОВОЇ НАПРУГИ ПРИ АПЕРІОДИЧНОМУ ЗАРЯДЖАННІ ВІД ДЖЕРЕЛА ПОСТІЙНОЇ НАПРУГИ - Супруновська, Н.І.; Щерба, А.A. (Інститут електродинаміки Національної академії наук України, 2024)
An analysis of the transient processes during aperiodic charging of the capacitive energy storage (CES) of the electrical discharge installation (EDI) from the source of direct voltage (SDV) of the USDV was carried out under the condition of changing the initial voltage of the CES at the time of the start of charging. The dependences of energy characteristics (dose of energy that powers the capacitor, energy losses and efficiency) on the magnitude and sign (polarity) of the initial voltage CES were obtained. The energetically appropriate CES charge modes were determined. It is substantiated that increasing the initial voltage of the capacitor leads to an increase in the charging efficiency. The analysis of the ratio between the dose of energy that powers the CES during one charge cycle W*C and the energy of losses W*losses showed that the ratio W*C / W*losses increases with a change in the voltage U0C from –USDV to + USDV due to the fact that the energy of losses W*losses decreases faster than the dose of energy that powers the CES. References 11, Fig. 3, table 1.